P176 Are sexually transmitted infections associated with child sexual exploitation in under 16 year olds attending Genitourinary Medicine clinics in the UK?. (30th June 2016) - Ward, Chris; Hughes, Gwenda; Mitchell, Holly; Rogstad, Karen
Abstract : Background: Child sexual exploitation (CSE) is a challenging diagnosis to make, with few clinical signs or symptoms, and little evidence that markers such as sexually transmitted infections (STIs) are CSE predictors. Aim: To investigate associations between STIs and CSE risk factors. Methods: The genitourinary medicine clinic activity dataset (GUMCAD) was used to identify clinics with >18 STI diagnoses in 13–15 year-olds in 2012. Cases with confirmed bacterial or protozoal STIs were matched by age, gender and clinic with non-STI controls. Clinics provided details of CSE-related risk factors irrespective of STI presence through an on-line questionnaire. Associations between STI outcome and CSE-related risk factors were analysed using logistic regression. Results: 18/44 (40.9%) clinics contacted provided data on 466 13–15 year-olds; 414 (88.8%) were female, and 52 (11.2%) male. 98.6% were heterosexual, and 66.7% white British. There were 18 (3.9%) 13, 108 (23.2%) 14 and 340 (80.0%) 15 year-olds. In univariate analysis an STI diagnosis was significantly associated with: 'highly-likely' CSE (OR 9.00, p = 0.037), >1 partner (OR 5.50, p = 0.000), >1 attendance in 2012 (OR 3.79, p = 0.0000), safeguarding referral (OR 1.94, p = 0.022), other service involvement (OR 1.72, p = 0.031) and vulnerability (OR 1.64, p = 0.026). After adjustment, STI diagnosis was significantly associated with: Health Advisor review (OR 6.78, p = 0.000), >1 partner (OR 5.82, p = 0.002), >1 attendance (OR 3.72, p = 0.000) and looked after child (OR 3.43, p = 0.039). Discussion: The presence of a bacterial or protozoal STI is only weakly associated with CSE and should not be used to infer CSE in the absence of more compelling evidence.